A Leaf Sequencing Algorithm for Multileaf Collimator in Intensity Modulated Radiotherapy - C. L. Chow, James; Jia, Jing; Hui, Lin (Reports of Radiotherapy and Oncology, 2015)
Background: In intensity modulated radiotherapy (IMRT), leaf sequencing algorithm is used to control the multileaf collimator (MLC) to produce beam segments resulting in a beam intensity map for highly conformal dose coverage. Objectives: A novel leaf sequencing algorithm based on the Langer’s integer programming method is proposed. Methods: Our algorithm selected the horizontal or orthogonal leaf direction of beam intensity maps as per Xia and Verhey’s algorithm with a new constraint to optimize the MLC leaf travel distance (LTD). Results: Comparison among the leaf sequencing algorithms from Xia and Verhey, Langer et al. and ours, both Langer’s and our algorithms have lower monitor units (8 and 10) compared to 15 of Xia’s algorithm. For the number of segment and LTD, our new algorithm has the smallest number and distance (5 and 7 cm) compared to both the Xia’s and Langer’s algorithm (7 and 24 cm and 6 and 20 cm). This revealed that model modifications could yield better results according to three criteria namely, total number of monitor unit, number of segment and LTD. Conclusions: In conclusion of experimental comparison performed, our algorithm can generate photon beam in IMRT dose delivery with lower monitor unit, number of segment and LTD compared to the Xia’s and Langer’s algorithm.